Estimates of Components of Variance, Genetic Gain and Heritability for Growth, Physiological and Biochemical Traits of Casuarina Clones under Varying Levels of Salinity Stress - Garg, Rakesh Kumar; Bassi, Palwinder; Nicodemus, A.; Choudhary, O. P.; Kaur, Nirmaljit (Indian Forester, 2021)
Eight clones of Casuarina (four of Casuarina junghuhniana and four of inter-specific hybrids of Casuarina equisetifolia Ã— C. junghuhniana) were subjected to saline water irrigation with different concentrations of NaCl viz., 0, 40, 80 and 120 mM. After twelve months of study period, significant genetic variability was observed among clones for growth, physiological and biochemical traits. High estimates of heritability with reasonable genetic advance were observed for plant height, collar diameter, plant fresh weight, plant dry weight and root length. Increase in genetic advance with increase in salinity levels (with highest genetic advance at 120 mM NaCl) coupled with high heritability estimates for all the characters suggested the potentiality of clonal material for improvement through selection for planting under saline soils.